2016
DOI: 10.1007/s11845-016-1430-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a web-based dietary assessment tool in early pregnancy

Abstract: Scores generated by this web-based DAT correlate with important nutrient intakes in pregnancy, supporting its use in estimating overall dietary quality among obstetric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Maternal body composition and dietary quality in pregnancy have been shown to affect long term health of the offspring ( 1 , 2 ) . We have previously shown that scores generated by the dietary assessment tool (DAT) are associated with nutrient intakes which are important to pregnancy outcome ( 3 ) . This study aimed to determine whether scores generated by the DAT were associated with maternal body weight and body composition in the first trimester.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal body composition and dietary quality in pregnancy have been shown to affect long term health of the offspring ( 1 , 2 ) . We have previously shown that scores generated by the dietary assessment tool (DAT) are associated with nutrient intakes which are important to pregnancy outcome ( 3 ) . This study aimed to determine whether scores generated by the DAT were associated with maternal body weight and body composition in the first trimester.…”
mentioning
confidence: 99%
“…This online survey elicited summary dietary intake data which was algorithmically evaluated and scored under a number of dietary domains, each representing one aspect of dietary quality. The dietary domain scores were condensed into a single percentage score for overall dietary quality as described previously ( 3 ) , with higher domain scores and higher overall scores representing more favourable dietary behaviour.…”
mentioning
confidence: 99%